Adsorption and Corrosion Inhibition Characteristics of Some Nicotinamide Derivatives on Mild Steel in Hydrochloric Acid Solution. (10th March 2014) - Chakravarthy, M. P.; Mohana, K. N.
Abstract : The present investigation includes the study of corrosion inhibition effect of N-(1H-Indol-3-ylmethylene)-nicotinamide (IMN) and N-(3, 4, 5-trimethoxy-benzylidene)-nicotinamide (TMN) on mild steel in 0.5 M HCl by mass loss and electrochemical measurements. The obtained results showed that inhibition efficiency increased with the increasing concentration of inhibitors and decreased with increase in temperature and immersion time. Potentiodynamic polarization curves indicate that both IMN and TMN were acting as mixed type of inhibitors. Langmuir adsorption isotherm model was employed to determine the equilibrium of adsorption for inhibiting process in both inhibitors. Nyquist plots revealed that, as the concentration of the inhibitors increases, double layer capacitance (C dl ) and corrosion current (i corr ) decreases, while polarization resistance (R p ) increases. Various thermodynamic parameters for the adsorption of inhibitors on mild steel were computed and discussed. The passive film formed on the metal surface was characterized by FTIR, EDX, and SEM.